Biodegradable nanogels for oral delivery of interferon for norovirus infection - Kim, Yunjeong; Thapa, Mahendra; Hua, Duy H.; Chang, Kyeong-Ok (My University, 2011)
Norwalk virus (NV) replicon-harboring cells have provided an excellent tool to the development of antivirals. Previously we demonstrated that the expression of replicon RNA and proteins was significantly reduced in the presence of various interferons (IFNs) including IFN-α and IFN-γ in a dose-dependent manner in the NV replicon-harboring cells and suggested IFNs could be therapeutic options for norovirus infection. It was also demonstrated that innate immunity including IFNs is crucial in the replication and pathogenicity of murine norovirus in vitro (RAW267.4 cells) and in vivo. IFNs have a short half life in vitro and in vivo due to low stability. Thus it is important to have a good delivery system to improve the stability of IFNs. Nanogels are nanosized networks of chemically cross-linked polymers that swell in physiologic solutions and provide improved stability and bioavailability to drugs. We have synthesized nanogels based on cross-linked polyethyleneimine (PEI)-polyethylenglycol (PEG). The PEI/PEG nanogels were further acetylated (AcNg) to reduce cellular penetration and cytotoxicity. The IFN-AcNg complex was prepared by incubating two components together at 4°C and lyophilization. The activities of IFN alone and IFN-AcNg were evaluated in the replicon-harboring cells and against murine norovirus-1 (MNV-1) in RAW267.4 cells. The AcNg improved the stability of IFN stored at 4°C, was well tolerated in the cells. Furthermore, the activity of IFN was significantly higher when combined with AcNg in the replicon-harboring cells and against MNV-1 in RAW267.4 cells. We concluded that AcNg may be pursued further as a vehicle for oral delivery of IFNs in norovirus infection.
Keywords: Antiviral; Interferon; Nanogel; Norwalk virus; Replicon-harboring cells; Murine norovirus